Comparison of the rare earth complexes iodides and polyiodides with biuret - A. D. Kornilov; M. S. Grigoriev; E. V. Savinkina (Тонкие химические технологии, 2022)
Objectives. Currently, several hundred polyiodide compounds have been synthesized and structurally characterized, but so far, no formation patterns for certain polyiodide ions have been revealed. The purpose of this work is to continue the search for formation regularities of polyiodides, including polyiodides of lanthanide complexes.Methods. Iodide and polyiodide of samarium complexes with biuret (BU), [Sm(BU)4]I3·BU·2H2O and [Sm(BU)4][I5][I]2, were first synthesized and characterized by X-ray diffraction analysis and infrared spectroscopy, respectively.Results. The obtained compounds complement the row of isostructural lanthanide (La–Gd) complexes. Structures of corresponding iodides and polyiodides were compared in detail. Both types of the compounds contain complex cations of the same composition; however, their structures differ significantly. The central atom coordination polyhedron can be described as a distorted square antiprism and a distorted dodecahedron, respectively. Even greater differences are observed in the outer sphere of complex compounds. The iodide compound crystals contain uncoordinated iodide ions, a biuret molecule and two water molecules. In the polyiodide compound, cations together with isolated I– ions form a three-dimensional framework with the channels, in which linear I5– ions are united in infinite linear chains by weak interactions.Conclusions. The replacement of an iodide ion with a polyiodide ion in complex compounds of lanthanides with BU leads to changes in both the inner sphere and the outer sphere of the cation complex, including the supramolecular level. The presence of iodine atom infinite linear chains in polyiodides allows expecting the presence of anisotropic electrical conductivity along this direction.